Cropland abandonment enhances soil inorganic nitrogen retention and carbon stock in China: A meta‐analysis. (11th September 2018) - Tian, Dashuan; Xiang, Yangzhou; Wang, Bingxue; Li, Meiling; Liu, Yanshu; Wang, Jinsong; Li, Zhaolei; Niu, Shuli
Abstract: Transforming cropland into a semi‐natural ecosystem is an effective approach to increase soil organic carbon (SOC) and nitrogen sequestration. However, we know little about large‐scale response patterns of SOC, soil inorganic nitrogen (SIN), and their interactions over long time of ecosystem restoration. Here, we conducted a meta‐analysis to examine changes in SOC, SIN, and their relationship along 50 year's ecosystem development from cropland transformation in China's 'Grain for Green' Programme. Our results showed that SOC and SIN were consistently enhanced by 57% and 35% with transformation, respectively. Similar with SOC, SIN had higher response magnitudes when cropland was restored to forests (47%) than to shrublands (36%) and grasslands (24%). Both SOC and SIN response ratios showed a quadratic relationship with precipitation. Moreover, we found a strong linear relationship ( R 2 = 0.36) between SOC and SIN response ratio, with the slope indicating a 0.43% increase in SIN per 1% of increasing SOC. This SIN retention capacity (the slope) significantly increased with restoration time but reduced with precipitation, temperature, and initial SOC. Restored forest had a lower SIN retention capacity than had shrubland and grassland. Overall, this study represents the first to regionally uncover SIN retention mechanism with increasing SOC during ecosystem development. It suggests that ecosystem restoration will contribute more to relieving serious environmental problems (i.e., N leaching and N2 O emission) by enhancing SIN retention in China's Grain for Green Programme.